Civil society participation and weak institutions :|the case of urban expansion in Istanbul - Kutlu Karasu, Rabia. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
Istanbul has experienced a multifaceted transformation between 2009 and 2019 with the introduction of various urban megaprojects. During this period, the urban expansion through the northern parts of the city has accelerated with the introduction of three megaprojects, i.e., the 3rd Bridge and the North Marmara Highway projects, the 3rd Airport project, and the Canal Istanbul project. This led to tensions between the state and the civil society over the top-down decision-making processes, the possible environmental costs of the projects, and the fate of the Northern Forests in Istanbul. Analyzing the period between 2009 and 2019, this thesis seeks answer to the question how the participatory prospects of environmental civil society organizations (CSOs) in the environmental governance of Istanbul has changed and what are implications of this change on the rise of the informal environmental movement organizations (EMOs) in the city. This thesis utilizes the data conducted from semi-structured interviews with the members of CSOs and extended document research. Based on this data, this thesis concluded that the civil society actors have experienced unprecedented difficulties in trying to reach the decision-making processes in the case of this three megaprojects because of the increasing weaknesses of formal participatory institutions. The institutional gridlocks they encountered have changed their capacities and strategies as well as encouraged the pursuit of political participation through more contentious forms of mobilization.
Keywords: Civil society.; Urban renewal -- İstanbul (Turkey)